A public law approach to investment treaty arbitration: Redressing the balance between investment protection and state regulation - Shoaib, Mohamed Adel (AUC Knowledge Fountain, 2016)
The ICSID has shifted the scope of investor-state disputes from domestic legal systems to international law realm. It assigns regulatory disputes between states and individuals to one-off private panels rather than public law courts. While investment treaty arbitration (ITA) combines the form and procedure of commercial arbitration, it performs under the substantive principles of public law. Since the ICSID does not set out the substantive rules governing investment disputes, investment treaty tribunals have constantly been the most dynamic zone of international investment law. Drawing on the ICSID neoliberal orientation, tribunals have interpreted and applied the substantive investment standards far beyond the consent of the treaty parties. They have largely intruded into domestic matters that lie within the host state sovereign authority. Moreover, they maintained a domestic normative scheme favourable to foreign investment that obviously exceeds international minimum standards of treatment. A minimal governmental regulatory action becomes an interference with the use of foreign private property that amounts to compensatory expropriation. The aim of this thesis is to reform investment treaty tribunals' law-making from within. Remoulding ITA as public law adjudication, this thesis sets out a comparative public law methodology for refining the content and scope of the open-ended standards for investment protection. It draws on the customary rules of the Vienna Convention on the Law of Treaties as a basis for interpreting investment treaty terms. This thesis seeks to reconceptualise the objectives of ITA under the ICSID legal framework. It emphasizes the correlation between investment protection and the host state's right to economic development. Further, it integrates rules on corporate social responsibility to equiponderate the host states' international responsibility vis-à-vis foreign investors. Finally, this thesis points out to the significance of incorporating general principles of law and judicial decisions as recognized sources of public international law into the practice of ITA. It argues that accommodating the principle of proportionality as a general principle of law in the tribunals' law-making process would help draw the line between investment protection and state regulation.